2017
DOI: 10.1161/strokeaha.117.016554
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthesia Versus Conscious Sedation for Endovascular Treatment of Acute Ischemic Stroke

Abstract: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01872884.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
274
4
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 347 publications
(303 citation statements)
references
References 26 publications
16
274
4
9
Order By: Relevance
“…In line with the randomized controlled trial-the AnStroke trial [19], we also found that conscious sedation and general anesthesia had similar clinical and safety outcomes. Consistent with the meta-analysis including IMS III and MR CLEAN trials [23], our study also showed that conscious sedation and general anesthesia The logistic regression model used for the determination of the propensity score included the following factors: age, sex, time from onset to visit, time from onset to treatment, time from onset to revascularization, occlusion site, collateral flow, ASPECTS, baseline NIHSS and intravenous thrombolysis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In line with the randomized controlled trial-the AnStroke trial [19], we also found that conscious sedation and general anesthesia had similar clinical and safety outcomes. Consistent with the meta-analysis including IMS III and MR CLEAN trials [23], our study also showed that conscious sedation and general anesthesia The logistic regression model used for the determination of the propensity score included the following factors: age, sex, time from onset to visit, time from onset to treatment, time from onset to revascularization, occlusion site, collateral flow, ASPECTS, baseline NIHSS and intravenous thrombolysis.…”
Section: Discussionsupporting
confidence: 86%
“…Collateral flow has been popularly known as an essential predictor of outcomes in recent years. In the AnStroke trial [19] and the present study, collateral flow was included for analysis, which consequently may attenuate the effects of anesthesia on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Í þeirri rannsókn var hins vegar enginn munur á blóðþrýstingi hjá þeim sem fengu svaefingu í stað slaevingar. 47 …”
Section: Svaefing Eða Slaeving Við Innaeðameðferðunclassified
“…shows that our search strategy finally incorporates 13 studies (3 RCTs(Löwhagen Hendén et al, 2017;Schönenberger et al, 2016;Simonsen et al, 2018) and 10 observational studies(Abou- Chebl et al, 2010;Abou-Chebl et al, 2014;Berg et al, 2015;Bracard et al, 2016;John et al, 2014;Jumaa et al, 2010;Shan et al, 2018;Slezak et al, 2017;Whalin et al, 2014)) available for analysis. A total of 2,129 patients underwent endovascular therapy for anterior ischemic stroke by CS, while 1,728 patients by GA.…”
mentioning
confidence: 99%